Impact of plant growth-promoting bacteria on the growth performance and resistance enzymes of tatsoi mustard in a hydroponic system - NABILLA ALYA ANASTASYA; ANTON MEILUS PUTRA; SHOLIKAH WIDYANITTA RACHMAWATI; IRISA TRIANTI; ADI SETIAWAN; ABDUL LATIEF ABADI; LUQMAN QURATA AINI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Anastasya NA, Putra AM, Rachmawati SW, Trianti I, Setiawan A, Abadi AL, Aini LQ. 2024. Impact of plant growth-promoting bacteria on the growth performance and resistance enzymes of tatsoi mustard in a hydroponic system. Biodiversitas 25: 3309-3317. Hydroponic system faces some problems in greenhouse cultivation including various biotic and abiotic stresses. Applying plant growth-promoting bacteria (PGPB) in hydroponic systems can alleviate those problems by serving as nutrient providers, plant growth promoters, and maintaining plant resilience. Therefore, the aim of this study was to evaluate PGPB strains for their potential to enhance plant growth and induce plant defense-related enzymes and compounds in tatsoi mustard plants (Brassica narinosa L.H. Bailey) when cultivated in a nutrient film technique (NFT) hydroponic system. The experiment was performed in a randomized block design (RBD) consisting of seven treatments and three replications. The treatments included P1: control with AB mix only; P2: Pseudomonas versuta UB36; P3: Pseudomonas aeruginosa UB52; P4: Pseudomonas lundensis UB53; P5: Pseudomonas migulae UB54; P6: Enterococcus gallinarum UB55 and; P7: Lysinibacillus fusiformis UB64. Based on the results, it was concluded that application of PGPB on tatsoi mustard promoted plant growth and production in hydroponic systems, which was shown in the treatment of P. ludensis UB53, P. migulae UB54, and L. fusiformis UB64. In addition, inoculation of PGPB strains induced resistance enzymes and compounds, namely phenylalanine ammonia-lyase (PAL), polyphenol oxidase (PPO) and peroxidase (PO) enzymes, and phenolic compounds in tatsoi mustard plants. P. ludensis UB53, P. migulae UB54, Enterococcus gallinarum UB55, and L. fusiformis UB64 showed higher activity in inducing plant resistance enzymes and compounds. Thus, these results suggested that PGPB improved tatsoi plant resistance against biotic as well as abiotic stresses and has the potential to be developed as an effective strategy for pest and disease management and increasing crop yield of tatsoi mustard grown in hydroponic systems.